Estimating the Basin of Attraction for the Power Flow Equations in Power Distribution Networks - Garces-Ruiz, Alejandro (IEEE transactions on power systems, 2024)
This letter presents an inner and outer estimation for the basin of attraction of the power flow in power distribution networks. The proposed methodology can be used to define the convergence region of the power flow algorithm and to estimate the minimum and maximum voltage of the grid without explicitly solving the power flow equations. Numerical experiments in the three-phase unbalanced IEEE 906 nodes test system show the use of the proposed methodology. Results include convergence analysis as well as a quasi-dynamic simulation considering 1440 different scenarios of load and renewable power generation.